The Effectiveness Of Use Of The Maternal And Child Health (Kia) Books On Knowledge About Pregnancy Care For Pregnant Women At The Eva Klurak Candi Sidoarjo Maternity Home - Juliana Fanumbi,; Retno Palupi Yonni Siwi,; Andariningsih,; Tutik Nushah, (Journal of Health Science Community, 2023)
The low level of knowledge about pregnancy care is influenced by a lack of information, which has an impact on utilization of KIA books. The aim of this research is to analyze The Effectiveness of Use of Kia Books On Knowledge About Pregnancy Care For Pregnant Women At The Eva Klurak Candi Sidoarjo Maternity Home. This research uses design correlational analytics with approach cross sectional. The population in this study was 40 respondents with a sample size of 36 respondents using the simple random sampling technique. Data collection by using questionnaires. Data analysis uses statistical tests Spearman Rank with a significant level of α = 0.05. The research results showed that of the 36 respondents, almost half of the respondents used KIA books in the high category, as many as 15 respondents (41.7%), most respondents had knowledge about good pregnancy care, as many as 26 respondents (81.2%).Results of data analysis using statistical tests Spearman Rank The P value obtained was < α 0.05 (0.000 < 0.05), which means that the use of KIA books was effective in increasing knowledge about pregnancy care for pregnant women at the Eva Klurak Candi Sidoarjo Maternity Home.The conclusion in this research is that the higher the use of KIA books, the better the knowledge about pregnancy care. The use of KIA books as a source of information and recording medical and is an important communication tool and information medium for health workers, pregnant women and families.